On the Exact Analysis of the Steady Creep of a Thin Tube Under Combined Loading - Boyle, J.; Spence, J. (Engineering Transactions, 1974)
An exact analysis is presented for the creep deformation of a long, thin, constant thickness circular cross-section cylindrical shell under various loadings. Results are presented in the form of a design chart which can be used for several load combinations, and as flexibility factors. Previous approximate analyses are discussed.